EFFECTIVITY OF XANTHONES IN MANGOSTEEN’S PERICARP TO INHIBITING FORMATION OF CANCER CELLS - Putri, Novita Dwiswara (Majority, 2015)
Abstract Indonesia has abundant biodiversity, including a medicinal plants. One of the medicinal plants is a Mangosteen (G. Mangostana L.) especially the pericarps. The pericarps of mangosteen produce xanthone whose levels can reach 123,97 mg/mls. In some studies it is known that xanthone had anti-oxidant and anti-cancer activity by preventing free radical and damage cells. Based on research reported that xanthone can inhibiting cancer cell growth and has an effect on proliferation of lymphocytes human in vitro. A potential anti-proliferation activity of 4 derivative xanthones (α-mangostin, β-mangostin, γ-mangostin, and methoxy- β-mangostin) derived from pericarps of Mangosteen. The potential of chemopreventive and chemotherapeutic properties of xanthones have been extensively investigated due to their inhibitory effect on every step in the process of carcinogenesis. These compounds are able to inhibit several molecular targets in the tumor cells, including kinases, cyclooxygenases, ribonucleotide reductase, and DNA polymerases. Keywords: anti-cancer, mangosteen’s pericarp, xanthone Abstrak Indonesia memiliki keanekaragaman hayati yang berlimpah, termasuk tanaman obat. Salah satunya adalah buah manggis (G. mangostana L.) terutama pemanfaatan pada kulitnya. Kulit buah manggis dapat menghasilkan senyawa xanton yang kadarnya dapat mencapai 123,97 mg/ml. Dalam beberapa penelitian diketahui bahwa senyawa xanton mempunyai aktivitas anti-oksidan dan anti-kanker dengan menangkal radikal bebas dan mencegah kerusakan sel. Berdasarkan hasil penelitian dilaporkan bahwa xanton dapat menghambat pertumbuhan sel kanker dan memiliki potensi aktivitas anti-proliferasi dari 4 turunan xanton (α-mangostin, β-mangostin, γ-mangostin, dan methoxy- β-mangostin) yang berasal dari kulit buah manggis. Sifat kemopreventif dan kemoterapi xanton telah banyak diteliti, salah satunya efek sebagai penghambat proses karsinogenesis. Senyawa ini mampu menghambat beberapa target molekul yang terdapat didalam sel-sel tumor termasuk kinase, siklooksigenase, ribonukleotida, reduktase dan DNA polymerase. Kata kunci: anti-kanker, kulit buah manggis, xanton